2022
DOI: 10.1038/s41467-022-29745-z
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine nucleotide redox potential in coronary smooth muscle couples myocardial blood flow to cardiac metabolism

Abstract: Adequate oxygen delivery to the heart during stress is essential for sustaining cardiac function. Acute increases in myocardial oxygen demand evoke coronary vasodilation and enhance perfusion via functional upregulation of smooth muscle voltage-gated K+ (Kv) channels. Because this response is controlled by Kv1 accessory subunits (i.e., Kvβ), which are NAD(P)(H)-dependent aldo-keto reductases, we tested the hypothesis that oxygen demand modifies arterial [NAD(H)]i, and that resultant cytosolic pyridine nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…We propose that these opposing functional impacts on the Kv1 function likely reflect different functionalities of Kvβ N-termini and their response to redox shifts, although this remains to be tested directly. In support of this, we recently reported that the activity of native Kv1 channels in coronary smooth muscle is upregulated in the presence of NADH and that this response requires the presence of catalytically active Kvβ2 [ 111 ].…”
Section: Control Of Vascular Tone and Smooth Muscle Phenotypementioning
confidence: 76%
“…We propose that these opposing functional impacts on the Kv1 function likely reflect different functionalities of Kvβ N-termini and their response to redox shifts, although this remains to be tested directly. In support of this, we recently reported that the activity of native Kv1 channels in coronary smooth muscle is upregulated in the presence of NADH and that this response requires the presence of catalytically active Kvβ2 [ 111 ].…”
Section: Control Of Vascular Tone and Smooth Muscle Phenotypementioning
confidence: 76%
“…For instance, small mesenteric arteries isolated from mice lacking either Kvβ1.1 or Kvβ2, which are highly abundant in vascular smooth muscle, exhibit normal levels of myogenic tone, as well as agonist-and K + -induced vasoconstriction (Ohanyan et al, 2021). Despite the observation that loss of Kvβ2 reduces the surface expression of Kv1.5 in coronary smooth muscle, this change was not associated with significant differences in I K density (Dwenger et al, 2022;Nystoriak et al, 2017;Ohanyan et al, 2021). Nonetheless, the inclusion of Kvβ2 promotes a shift in the voltage-dependence of activation towards more hyperpolarized membrane potentials, which may have important considerations in the modulation of voltage-sensitivity upon changes in cytosolic levels of NAD(P)H (Dwenger et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The Kvβ proteins are functional aldo–keto reductases that catalyse NAD(P)H‐dependent reduction of endogenous carbonyls and differentially regulate channel gating (Barski et al., 2009; Tipparaju et al., 2008; Tipparaju et al., 2012). Our recent work showed that the catalytic function of Kvβ2 links pyridine nucleotide redox conditions with Kv1‐mediated vasodilatation (Dwenger et al., 2022). Nonetheless, the physiological relevance of this phenomenon in the metabolic sensing capacity of the resistance vasculature is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of declining ATP in CMs, activation in ATP‐sensitive K + channels could thereby be transmitted to the local capillary network to induce upstream arteriolar vasodilatation and increase oxygen delivery to the affected CMs. At the level of coronary arteries and arterioles, other investigations have shown that acute increases in CM workload and oxygen demand are transmitted by an unknown mechanism to proximal VSMCs, culminating in altered vascular redox pairs (Dwenger et al., 2022). As discussed at the Symposium, acute elevation of cytosolic NADH levels in VSMCs as a result of enhanced myocardial oxygen demand is, in turn, sensed by smooth muscle Kv1 channels, which are differentially regulated by cellular redox via associating heteromeric β subunit assemblies (Dwenger et al., 2018; Ohanyan et al., 2021).…”
Section: Contribution Of Cell Diversity To Cardiovascular Remodelling...mentioning
confidence: 99%